Dielectric, multilayer ceramic capacitor, method for manufacturing dielectric, and method for manufacturing multilayer ceramic capacitor
By using Zr, Eu and Mn doped bacilite crystal particles in the dielectric layer of the multi-layer ceramic capacitor to form a core shell structure, the problem of insufficient reliability at high temperatures in the prior art is solved, and high reliability and excellent capacitance temperature characteristics are achieved at high temperatures.
Patent Information
- Application Number
- JP2021105342
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2041-06-25
AI Technical Summary
The dielectric layer of existing multi-layer ceramic capacitors is insufficient in reliability at high temperatures and is difficult to meet the X8R capacitance characteristics of high temperature applications.
Barium titanate crystal particles containing Zr, Eu and Mn are used to form a core shell structure, where the Zr concentration in the shell part is higher than that of the core part, and the atomic concentration ratio of Zr/Ti, Eu/Ti and Mn/Ti, as well as the median diameter of the crystal particles are controlled to achieve high temperature stability and capacitance characteristics.
It realizes high reliability and excellent capacitance temperature characteristics of multi-layer ceramic capacitors at high temperatures, meeting the X8R standard.
Smart Images

Figure 0007649598000003 
Figure 0007649598000004 
Figure 0007649598000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a dielectric, a multilayer ceramic capacitor, a method for manufacturing a dielectric, and a method for manufacturing a multilayer ceramic capacitor. [Background technology]
[0002] Multilayer ceramic capacitors are used to remove noise in high-frequency communication systems, such as mobile phones. Multilayer ceramic capacitors are also used in electronic circuits that affect human life, such as in-vehicle electronic control devices. Since high reliability is required for multilayer ceramic capacitors, techniques for improving reliability have been disclosed (for example, see Patent Documents 1 to 5). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP2017-114751 Public Relations [Patent Document 2] JP 2018-90458 A [Patent Document 3] JP 2019-131438 A [Patent Document 4] JP 2016-169130 A [Patent Document 5] JP 2015-187969 A Summary of the Invention [Problem to be solved by the invention]
[0004] For the dielectric of multilayer ceramic capacitors, sintered bodies with a core-shell structure have been used, in which the core is made of barium titanate and the shell is filled with various additives. This is because it is possible to obtain a material with excellent capacitance-temperature characteristics and a stable microstructure even during the sintering process. A typical additive that makes up the shell is magnesium (Mg). However, Mg is a simple acceptor with no valence fluctuation, and because it is electrically neutral, it generates oxygen defects that are known to have a negative effect on the reliability of multilayer ceramic capacitors, so there was a problem that the reliability was not high enough for high-reliability applications.
[0005] Next, for high reliability applications, multilayer ceramic capacitors that can be used at high temperatures up to 150°C are required. However, barium titanate, the main component of the dielectric layer, has a Curie point of about 125°C, and the capacitance decreases significantly at temperatures above the Curie point. Therefore, unless special measures are taken, it is not possible to meet the EIA standard temperature characteristic X8R (the rate of change in capacitance from -55°C to 150°C is within ±15% based on the capacitance at 25°C). As a remedy, there is a method of satisfying X8R by adding Yb (ytterbium) to the dielectric layer to shift the Curie point to the high temperature side, but since Yb acts as an acceptor, it is not reliable enough for high reliability applications, just like Mg mentioned above. In addition, BaTi, which has a high Curie point, 2 O 5 (470℃) BaTiO 3 There is also a method to mix BaTi 2 O 5 has a small relative dielectric constant at room temperature and cannot exhibit a high capacity.
[0006] The present invention has been made in consideration of the above problems, and has an object to provide a dielectric, a multilayer ceramic capacitor, a method for manufacturing a dielectric, and a method for manufacturing a multilayer ceramic capacitor that are capable of achieving both a long life and excellent capacitance-temperature characteristics. [Means for solving the problem]
[0007] The dielectric of the present invention includes a plurality of crystal particles mainly composed of barium titanate, and contains Zr, Eu, and Mn as additives, at least any of the plurality of crystal particles has a core-shell structure having a core portion mainly composed of barium titanate and a shell portion mainly composed of barium titanate and having a higher Zr concentration than the core portion, the Zr / Ti atomic concentration ratio is 0.02 or more and 0.10 or less, the Eu / Ti atomic concentration ratio is 0.001 or more and 0.03 or less, and the Mn / Ti atomic concentration ratio is 0.005 or more and 0.05 or less, the total atomic concentration of other rare earth elements is smaller than the atomic concentration of Eu, and the median diameter of the plurality of crystal particles is 200 nm or more and 400 nm or less.
[0008] The dielectric may not contain any rare earth elements other than Eu.
[0009] The multilayer ceramic capacitor according to the present invention has a laminated structure in which dielectric layers and internal electrode layers are alternately laminated, has a substantially rectangular parallelepiped shape, and is formed so that a plurality of the laminated internal electrode layers are alternately exposed on two different surfaces, and the dielectric layer in a capacity region where the internal electrode layers exposed on the two different surfaces face each other contains a plurality of crystal grains mainly composed of barium titanate, and contains Zr, Eu, and Mn as additives, and at least one of the plurality of crystal grains is a barium titanate-based crystal grain. The magnetic material has a core-shell structure including a core portion and a shell portion mainly composed of barium titanate and having a higher Zr concentration than the core portion, the Zr / Ti atomic concentration ratio is 0.02 or more and 0.10 or less, the Eu / Ti atomic concentration ratio is 0.001 or more and 0.03 or less, the Mn / Ti atomic concentration ratio is 0.005 or more and 0.05 or less, the total atomic concentration of other rare earth elements is smaller than the atomic concentration of Eu, and the median diameter of the plurality of crystal particles is 200 nm or more and 400 nm or less.
[0010] The multilayer ceramic capacitor may satisfy X8R characteristics.
[0011] The method for producing a dielectric according to the present invention is characterized in that a dielectric green sheet containing barium titanate powder, containing Zr, Eu and Mn as additives, having a Zr / Ti atomic concentration ratio of 0.02 or more and 0.10 or less, an Eu / Ti atomic concentration ratio of 0.001 or more and 0.03 or less, an Mn / Ti atomic concentration ratio of 0.005 or more and 0.05 or less, and having a total atomic concentration of other rare earth elements smaller than the atomic concentration of Eu, is heated and fired at a heating rate of 5000°C / h or more and 10000°C / h or less to obtain a dielectric containing a plurality of crystal grains mainly composed of barium titanate, the plurality of crystal grains having a median diameter of 200 nm or more and 400 nm or less.
[0012] The method for producing a multilayer ceramic capacitor according to the present invention is characterized in that it includes a step of obtaining a ceramic laminate by stacking a plurality of lamination units, each of which is printed with a metal conductive paste, on a dielectric green sheet that contains barium titanate powder, Zr, Eu and Mn as additives, has a Zr / Ti atomic concentration ratio of 0.02 or more and 0.10 or less, an Eu / Ti atomic concentration ratio of 0.001 or more and 0.03 or less, an Mn / Ti atomic concentration ratio of 0.005 or more and 0.05 or less, and has a total atomic concentration of other rare earth elements that is smaller than the atomic concentration of Eu, and a step of firing the ceramic laminate by heating at a heating rate of 5000°C / h or more and 10000°C / h or less, so that a dielectric layer containing a plurality of crystal particles mainly composed of barium titanate, the plurality of crystal particles having a median diameter of 200 nm or more and 400 nm or less, is formed from the dielectric green sheet. Effect of the Invention
[0013] According to the present invention, it is possible to provide a dielectric, a multilayer ceramic capacitor, a method for manufacturing a dielectric, and a method for manufacturing a multilayer ceramic capacitor that are capable of achieving both a long life and excellent capacitance-temperature characteristics. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is a partial cross-sectional perspective view of a multilayer ceramic capacitor. [Diagram 2]2 is a cross-sectional view taken along line AA in FIG. 1. [Diagram 3] FIG. 2 is a cross-sectional view taken along line BB in FIG. [Figure 4] FIG. 2A is a diagram illustrating an example of a core-shell particle, and FIG. 2B is a schematic cross-sectional view of a dielectric layer. [Diagram 5] 1A to 1C are diagrams illustrating a flow of a method for manufacturing a multilayer ceramic capacitor. [Figure 6] 4 is an SEM image of a cross section of the dielectric layers and internal electrode layers in the capacitance region of Example 1. [Figure 7] This is a TEM image of the dielectric layer in the capacitance region. [Figure 8] (a) shows the measurement results of the TEM-EDS analysis of the shell portion, and (b) shows the measurement results of the TEM-EDS analysis of the core portion. [Figure 9] 13 is an SEM image of a cross section of the dielectric layers and internal electrode layers in the capacitance region of Comparative Example 12. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment will be described with reference to the drawings.
[0016] (Embodiment) FIG. 1 is a partial cross-sectional perspective view of a multilayer ceramic capacitor 100 according to an embodiment. FIG. 2 is a cross-sectional view taken along line AA in FIG. 1. FIG. 3 is a cross-sectional view taken along line BB in FIG. 1. As illustrated in FIGS. 1 to 3, the multilayer ceramic capacitor 100 includes a laminated chip 10 having a substantially rectangular parallelepiped shape, and external electrodes 20a, 20b provided on any two opposing end faces of the laminated chip 10. Of the four faces of the laminated chip 10 other than the two end faces, the two faces other than the top and bottom faces in the stacking direction are referred to as side faces. The external electrodes 20a, 20b extend on the top, bottom and two side faces in the stacking direction of the laminated chip 10. However, the external electrodes 20a, 20b are spaced apart from each other.
[0017] The laminated chip 10 has a configuration in which dielectric layers 11 containing a ceramic material that functions as a dielectric and internal electrode layers 12 containing a base metal material are alternately laminated. The edges of the internal electrode layers 12 are alternately exposed to the end face on which the external electrode 20a of the laminated chip 10 is provided and the end face on which the external electrode 20b is provided. As a result, each internal electrode layer 12 is alternately conductive to the external electrode 20a and the external electrode 20b. As a result, the laminated ceramic capacitor 100 has a configuration in which a plurality of dielectric layers 11 are laminated via the internal electrode layers 12. In addition, in the laminate of the dielectric layers 11 and the internal electrode layers 12, the internal electrode layers 12 are arranged on the outermost layer in the lamination direction, and the upper and lower surfaces of the laminate are covered by the cover layer 13. The cover layer 13 is mainly composed of a ceramic material. For example, the material of the cover layer 13 is the same as that of the dielectric layers 11 and the ceramic material. It should be noted that the configuration is not limited to those shown in FIGS. 1 to 3, so long as the internal electrode layers 12 are exposed on two different surfaces and are electrically connected to different external electrodes.
[0018] The size of the multilayer ceramic capacitor 100 is, for example, 0.25 mm in length, 0.125 mm in width, and 0.125 mm in height, or 0.4 mm in length, 0.2 mm in width, and 0.2 mm in height, or 0.6 mm in length, 0.3 mm in width, and 0.3 mm in height, or 1.0 mm in length, 0.5 mm in width, and 0.5 mm in height, or 3.2 mm in length, 1.6 mm in width, and 1.6 mm in height, or 4.5 mm in length, 3.2 mm in width, and 2.5 mm in height, but is not limited to these sizes.
[0019] The internal electrode layer 12 is mainly composed of a base metal such as Ni (nickel), Cu (copper), or Sn (tin). Noble metals such as Pt (platinum), Pd (palladium), Ag (silver), or Au (gold) or alloys containing these may be used as the internal electrode layer 12. The thickness of the internal electrode layer 12 is, for example, 0.1 μm to 3 μm, 0.1 μm to 1 μm, or 0.1 μm to 0.5 μm.
[0020] The dielectric layer 11 is, for example, a compound represented by the general formula ABO 3The main phase of the ceramic material is a perovskite structure represented by the formula: 3-α In this embodiment, the ceramic material contains at least Ba (barium) in the A site and at least Ti (titanium) in the B site. The B site may contain Zr (zirconium). The thickness of the dielectric layer 11 is, for example, 0.2 μm to 10 μm, 0.2 μm to 5 μm, or 0.2 μm to 2 μm.
[0021] 2, a region where the internal electrode layer 12 connected to the external electrode 20a and the internal electrode layer 12 connected to the external electrode 20b face each other is a region that generates capacitance in the multilayer ceramic capacitor 100. Therefore, the region that generates capacitance is referred to as a capacitance region 14. In other words, the capacitance region 14 is a region where adjacent internal electrode layers 12 connected to different external electrodes face each other.
[0022] The region where the internal electrode layers 12 connected to the external electrode 20a face each other without an internal electrode layer 12 connected to the external electrode 20b being interposed therebetween is referred to as the end margin 15. The region where the internal electrode layers 12 connected to the external electrode 20b face each other without an internal electrode layer 12 connected to the external electrode 20a being interposed therebetween is also the end margin 15. In other words, the end margin 15 is a region where the internal electrode layers 12 connected to the same external electrode face each other without an internal electrode layer 12 connected to a different external electrode being interposed therebetween. The end margin 15 is a region that does not generate capacitance.
[0023] 3, in the laminated chip 10, the regions extending from the two side surfaces of the laminated chip 10 to the internal electrode layers 12 are referred to as side margins 16. That is, the side margins 16 are regions provided to cover the ends of the multiple internal electrode layers 12 stacked in the above-mentioned laminated structure that extend to the two side surfaces. The side margins 16 are also regions that do not generate electrical capacitance.
[0024] In the capacitance region 14 of such a multilayer ceramic capacitor 100, when at least a portion of the barium titanate crystal grains contained in the dielectric layer 11 have a core-shell structure, the dielectric layer 11 in the capacitance region 14 has a high dielectric constant, excellent temperature characteristics, and a stable microstructure coexists.
[0025] A typical additive that constitutes the shell is Mg. However, Mg is a simple acceptor whose valence does not change, and it dissolves in the barium titanate of the dielectric layer 11 to generate oxygen defects, which reduces the reliability.
[0026] Therefore, in this embodiment, in the capacitance region 14, at least a part of the crystal grains of barium titanate contained in the dielectric layer 11 has a core-shell structure with a core portion mainly composed of barium titanate and a Zr (zirconium) diffusion layer as a shell portion. The shell portion is mainly composed of barium titanate.
[0027] As illustrated in FIG. 4(a), the core-shell particle 30 includes a substantially spherical core portion 31 and a shell portion 32 surrounding and covering the core portion 31. The core portion 31 is a crystalline portion in which the additive compound is not dissolved or in which the amount of the additive compound dissolved is small. The shell portion 32 is a crystalline portion in which the additive compound is dissolved and has a higher additive compound concentration than the additive compound concentration in the core portion 31. In this embodiment, the Zr concentration in the shell portion 32 is higher than the Zr concentration in the core portion 31. Alternatively, Zr is diffused in the shell portion 32, and Zr is not diffused in the core portion 31.
[0028] Fig. 4(b) is a schematic cross-sectional view of the dielectric layer 11. As illustrated in Fig. 4(b), the dielectric layer 11 includes a plurality of crystal grains 17 of the main component ceramic. At least some of these crystal grains 17 are the core-shell particles 30 described in Fig. 4(a). By covering the core portion 31 with the shell portion 32 having a high Zr concentration and high reduction resistance, it is possible to obtain a highly reliable material that has a stable structure while maintaining a high dielectric constant.
[0029] In addition, when Zr is diffused and dissolved in barium titanate, the Curie temperature of barium titanate is lowered, so if the Zr diffusion layer is made thicker than necessary, the capacitance change rate at high temperatures increases, and the multilayer ceramic capacitor 100 may not satisfy the X8R characteristics. In general, Zr diffuses and dissolves in barium titanate, causing rapid grain growth, so it is difficult to realize the X8R characteristics by restricting the thickness of the diffusion layer and suppressing grain growth. For example, if the temperature rise rate in the sintering process is about 10°C / h, the diffusion of rare earths is excessively promoted and fully dissolved particles are formed. In this case, since the solid solution of Zr and rare earth elements progresses, a long life can be obtained, but the dielectric constant is low, the sintering stability is reduced, and the temperature characteristic of the capacitance tends to deteriorate. In this embodiment, the Zr diffusion distance is limited and the Zr concentration in the shell portion 32 is higher than that in the core portion 31, so that the multilayer ceramic capacitor 100 satisfies the X8R characteristics.
[0030] If the Zr / Ti atomic concentration ratio is too small in the dielectric layer 11 of the capacitance region 14, the core-shell structure having a core part with a low Zr concentration and a shell part with a high Zr concentration cannot be maintained, local abnormal growth occurs, and a long life and X8R characteristics may not be obtained. Therefore, in this embodiment, a lower limit is set for the Zr / Ti atomic concentration ratio. Specifically, in the dielectric layer 11 of the capacitance region 14, the Zr / Ti atomic concentration ratio is set to 0.02 or more. In this case, the grain size of the crystal grains 17 becomes almost uniform, and a stable core-shell structure having an element distribution in which a high concentration of Zr is arranged in the shell part 32 can be formed. The Zr / Ti atomic concentration ratio is preferably 0.03 or more, and more preferably 0.04 or more.
[0031] On the other hand, if the Zr / Ti atomic concentration ratio in the dielectric layer 11 in the capacitance region 14 is too large, the relative dielectric constant of the dielectric layer 11 becomes low (for example, 1500 or less), and there is a risk that the X8R characteristics will not be satisfied. Therefore, in this embodiment, an upper limit is set for the Zr / Ti atomic concentration ratio. Specifically, the Zr / Ti atomic concentration ratio in the dielectric layer 11 in the capacitance region 14 is set to 0.10 or less. This makes it possible to obtain a sufficient relative dielectric constant. The Zr / Ti atomic concentration ratio is preferably 0.08 or less, and more preferably 0.06 or less.
[0032] However, doping the dielectric layer 11 with Zr expands the lattice constant of the barium titanate crystal, and rare earth elements such as Ho (holmium), Dy (dysprosium), and Y (yttrium), which are essential for the lifetime, are dissolved in greater amounts in the B site than in the A site, resulting in an excess of acceptors, and therefore the effect of improving the lifetime is limited.
[0033] Therefore, the inventors have investigated rare earth elements with large ionic radii that easily dissolve in the A site of barium titanate, and have found that adding Eu (europium) improves the life by about one order of magnitude compared to rare earth elements such as Ho, Dy, and Y. The reason why the life is improved by adding Eu has not been fully elucidated, but it is believed that Eu is stable in divalent and trivalent states, and has the largest ionic radius among rare earth element ions that are stable in divalent states, so it selectively dissolves in the A site. Note that rare earth elements other than Eu are stable in trivalent states and unstable in divalent states.
[0034] Table 1 shows the ionic radius of each rare earth element with six coordinations. The source of Table 1 is "RD Shannon, Acta Crystallogr., A32, 751 (1976)". [Table 1]
[0035] Eu also dissolves more in the shell portion 32 than in the core portion 31. Therefore, the Eu concentration in the shell portion 32 is higher than the Eu concentration in the core portion 31.
[0036] If the Eu / Ti atomic concentration ratio in the dielectric layer 11 of the capacitance region 14 is too small, a sufficiently long life may not be obtained. Therefore, in this embodiment, a lower limit is set for the Eu / Ti atomic concentration ratio. Specifically, the Eu / Ti atomic concentration ratio in the dielectric layer 11 of the capacitance region 14 is set to 0.001 or more. The Eu / Ti atomic concentration ratio is preferably 0.005 or more, and more preferably 0.01 or more.
[0037] On the other hand, if the Eu / Ti atomic concentration ratio in the dielectric layer 11 in the capacitance region 14 is too large, the dielectric layer 11 may become a semiconductor, and a long life may not be obtained. Therefore, in this embodiment, an upper limit is set for the Eu / Ti atomic concentration ratio. Specifically, the Eu / Ti atomic concentration ratio in the dielectric layer 11 in the capacitance region 14 is set to 0.03 or less. The Eu / Ti atomic concentration ratio is preferably 0.025 or less, and more preferably 0.02 or less.
[0038] However, if a part of Eu dissolves in the A site as a trivalent ion, it may become a donor and deteriorate the insulating properties. The inventors have found that co-addition of Mn (manganese), which has the function of reducing excess electrons, is effective in this regard. Mn not only improves the insulating properties, but also increases the valence by performing a reoxidation treatment, which reduces oxygen defects and further improves the life. The entire amount of Mg, which is a simple acceptor, may be replaced with Mn, or a small amount of Mg may be left to utilize the grain size suppressing effect of Mg. In either case, Mn is made to play the role of an acceptor, and Mg is minimized in accordance with the design of the structure and other properties.
[0039] If the Mn / Ti atomic concentration ratio in the dielectric layer 11 in the capacitance region 14 is too small, there may be a shortage of acceptors in the dielectric layer 11, and a long life may not be obtained by converting the dielectric layer 11 into a semiconductor. Therefore, in this embodiment, a lower limit is set for the Mn / Ti atomic concentration ratio. Specifically, the Mn / Ti atomic concentration ratio in the dielectric layer 11 in the capacitance region 14 is set to 0.005 or more. The Mn / Ti atomic concentration ratio is preferably 0.01 or more, and more preferably 0.02 or more.
[0040] On the other hand, if the Mn / Ti atomic concentration ratio is too large in the dielectric layer 11 of the capacitance region 14, the amount of oxygen vacancies may become excessive due to an excess amount of acceptors, which may shorten the life. Therefore, in this embodiment, an upper limit is set for the Mn / Ti atomic concentration ratio. Specifically, the Mn / Ti atomic concentration ratio in the dielectric layer 11 of the capacitance region 14 is set to 0.05 or less. The Mn / Ti atomic concentration ratio is preferably 0.04 or less, and more preferably 0.03 or less.
[0041] In addition, when additives such as Zr and Mn are dissolved in barium titanate, the Curie temperature of barium titanate may shift to a lower temperature side below 125°C, which may deteriorate the capacitance change rate at high temperatures. On the other hand, in this embodiment, the Curie point shifts to a higher temperature side (e.g., 130°C) above 125°C, suppressing deterioration of the capacitance change rate at high temperatures and allowing the multilayer ceramic capacitor 100 to satisfy the X8R characteristics. Although the reason for the shift of the Curie point to a higher temperature side has not been fully elucidated, it is presumed that the reason is that the core portion 31 has a contracted crystal lattice due to a part of Eu being dissolved in the core portion 31 beyond the shell portion 32, and the shell portion 32 has an expanded crystal lattice due to the diffusion of a high concentration of Zr-rich additive, which generates internal stress at the interface between them.
[0042] If the crystal grain size in the dielectric layer 11 is too small or too large, the capacitance change rate increases, and the multilayer ceramic capacitor 100 may not have X8R characteristics. Therefore, in this embodiment, a lower limit and an upper limit are set for the median diameter of the crystal grains 17 in the dielectric layer 11 in the capacitance region 14. Specifically, the median diameter of the crystal grains 17 in the dielectric layer 11 in the capacitance region 14 is set to 200 nm or more and 400 nm or less. By setting the median diameter within this range, the temperature change rate above the Curie point can be suppressed. The median diameter of the crystal grains 17 in the dielectric layer 11 in the capacitance region 14 is preferably 250 nm or more, and more preferably 300 nm or more. On the other hand, the median diameter of the crystal grains 17 in the dielectric layer 11 in the capacitance region 14 is preferably 375 nm or less, and more preferably 350 nm or less.
[0043] Next, if the amount of rare earth elements other than Eu added to the dielectric layer 11 of the capacitance region 14 is too large, the effect of improving the lifespan by Eu is weakened, and there is a risk that a sufficient lifespan cannot be obtained. Therefore, in this embodiment, an upper limit is set for the amount of rare earth elements other than Eu added. Specifically, the atomic concentration of the rare earth elements other than Eu is made lower than the atomic concentration of Eu in the dielectric layer 11 of the capacitance region 14. When there are multiple types of rare earth elements other than Eu, the total atomic concentration of the multiple types of rare earth elements is made lower than the atomic concentration of Eu.
[0044] As described above, according to this embodiment, at least any of the crystal particles in the dielectric layer 11 in the capacitance region 14 has a core-shell structure including a core portion 31 mainly composed of barium titanate and a shell portion 32 mainly composed of barium titanate and having a higher Zr concentration than the core portion 31, and in the dielectric layer 11 in the capacitance region 14, the Zr / Ti atomic concentration ratio is 0.02 or more and 0.10 or less, the Eu / Ti atomic concentration ratio is 0.001 or more and 0.03 or less, the Mn / Ti atomic concentration ratio is 0.005 or more and 0.05 or less, the total atomic concentration of other rare earth elements is smaller than the atomic concentration of Eu, and the median diameter of the crystal particles 17 in the dielectric layer 11 in the capacitance region 14 is 200 nm or more and 400 nm or less, thereby making it possible to achieve both a long life and excellent capacitance-temperature characteristics.
[0045] Next, a description will be given of a method for manufacturing the multilayer ceramic capacitor 100. FIG.
[0046] (Raw powder production process) First, a dielectric material is prepared for forming the dielectric layer 11. The A-site elements and B-site elements contained in the dielectric layer 11 are usually ABO 3 The dielectric layer 11 is formed of a sintered body of BaTiO particles. 3 BaTiO is a tetragonal compound with a perovskite structure and exhibits a high dielectric constant. 3 Generally, barium titanate can be obtained by reacting a titanium raw material such as titanium dioxide with a barium raw material such as barium carbonate to synthesize barium titanate. Various methods have been known so far as a method for synthesizing the main component ceramic of the dielectric layer 11, such as a solid phase method, a sol-gel method, a hydrothermal method, etc. In this embodiment, any of these methods can be adopted.
[0047] A predetermined additive compound is added to the obtained ceramic powder according to the purpose. Examples of the additive compound include oxides of Zr, Mg, Mn, V (vanadium), Cr (chromium), and Eu, as well as oxides or glasses of Co (cobalt), Ni, Li (lithium), B (boron), Na (sodium), K (potassium), and Si (silicon). If necessary, oxides of rare earth elements other than Eu (Sc (scandium), Y, La (lanthanum), Ce (cerium), Pr (praseodymium), Nd (neodymium), Pm (promethium), Sm (samarium), Gd (gadolinium), Tb (terbium), Dy, Ho, Er (erbium), Tm (thulium), Yb, and Lu (lutetium)) may be added.
[0048] For example, a compound containing an additive compound is wet mixed with a ceramic raw material powder, and then dried and pulverized to prepare a ceramic material. For example, the ceramic material obtained as described above may be pulverized to adjust the particle size as necessary, or may be combined with a classification process to adjust the particle size. A dielectric material is obtained by the above steps. In the dielectric material, the Zr / Ti atomic concentration ratio is set to 0.02 to 0.10, the Eu / Ti atomic concentration ratio is set to 0.001 to 0.03, the Mn / Ti atomic concentration ratio is set to 0.005 to 0.05, and the total atomic concentration of other rare earth elements is made smaller than the atomic concentration of Eu.
[0049] (Lamination process) Next, a binder such as polyvinyl butyral (PVB) resin, an organic solvent such as ethanol or toluene, and a plasticizer are added to the obtained dielectric material and wet mixed. The obtained slurry is used to coat a strip-shaped dielectric green sheet, for example, 0.5 μm or more thick, on a substrate by, for example, a die coater method or a doctor blade method, and then dried.
[0050] Next, a metal conductive paste containing an organic binder for forming internal electrodes is printed on the surface of the dielectric green sheet by screen printing, gravure printing, or the like to arrange an internal electrode layer pattern that is alternately led to a pair of external electrodes with different polarities. Ceramic particles are added to the metal conductive paste as a co-material. The main component of the ceramic particles is not particularly limited, but is preferably the same as the main component ceramic of the dielectric layer 11. For example, BaTiO 3 may be uniformly dispersed.
[0051] Thereafter, the dielectric green sheet on which the internal electrode layer pattern is printed is punched out to a predetermined size, and the punched dielectric green sheet is laminated by a predetermined number of layers (for example, 100 to 1000 layers) with the base material peeled off so that the internal electrode layers 12 and the dielectric layers 11 are alternately arranged, and the edges of the internal electrode layers 12 are alternately exposed at both end faces in the length direction of the dielectric layers 11 and alternately drawn out to a pair of external electrodes 20a, 20b with different polarities. Cover sheets for forming the cover layer 13 are pressure-bonded to the top and bottom of the laminated dielectric green sheets, and the laminated dielectric green sheets are cut to a predetermined chip size (for example, 1.0 mm x 0.5 mm).
[0052] (Firing process) The ceramic laminate thus obtained was subjected to 2 After the binder removal treatment, a metal paste that will become the underlayer of the external electrodes 20a and 20b is applied by a dipping method, and the oxygen partial pressure is 10 -12 MPa~10 -9 The mixture is fired in a reducing atmosphere at 1160°C to 1280°C under reduced pressure of MPa for 5 to 10 minutes.
[0053] If the heating rate is set to a slow rate of about 10°C / h, the diffusion of rare earth elements and Zr is promoted in the dielectric material barium titanate, and all solid solution particles are formed. In this case, a long life is obtained, but the dielectric constant is low, and the sintering stability and the capacitance-temperature characteristic tend to deteriorate. Therefore, in this embodiment, by setting the heating rate to 5000°C / h or more and 10000°C / h or less (for example, 6000°C / h), it is possible to suppress the diffusion of Zr and form a core-shell structure with a large concentration gradient of Zr.
[0054] In addition, by adjusting the sintering conditions such as the particle size of the barium titanate powder in the dielectric material, the sintering temperature, and the sintering time, the median diameter of the crystal grains 17 in the dielectric layer 11 of the capacitance region 14 obtained after sintering is adjusted to 200 nm or more and 400 nm or less.
[0055] (Reoxidation treatment process) In order to return oxygen to the partially reduced main phase of the dielectric layer 11, which was fired in a reducing atmosphere, the dielectric layer 11 was fired in a reducing atmosphere at about 1000° C. under N 2 Heat treatment may be performed in a mixture of oxygen and water vapor, or in air at 500°C to 700°C. This process is called the reoxidation process.
[0056] (Plating process) Thereafter, the underlayers of the external electrodes 20a, 20b are coated with a metal such as Cu, Ni, Sn, etc. by plating. Through the above steps, the multilayer ceramic capacitor 100 is completed. EXAMPLES
[0057] The multilayer ceramic capacitor according to the embodiment was fabricated and its characteristics were examined.
[0058] Example 1 BaTiO 3 In contrast, ZrO 2 , MnCO 3Various additives such as Eu oxide and organic solvent were added to the mixture in a predetermined ratio, and the mixture was mixed and ground with φ0.5mm zirconia beads. The Zr / Ti atomic concentration ratio was set to 0.04. The Eu / Ti atomic concentration ratio was set to 0.01. The Mn / Ti atomic concentration ratio was set to 0.03. No rare earth elements were added except for Eu. A dielectric green sheet was coated with the slurry obtained by adding a binder, and an internal electrode pattern was printed with Ni paste, laminated, and cut into a 1005 shape to produce a 1005-shaped ceramic laminate. The ceramic laminate was heated to 1230°C at a heating rate of 6000°C / h and subjected to high-speed firing. In order to reduce oxygen defects caused by reduction firing, the fired multilayer ceramic capacitor was subjected to reoxidation treatment at 1000°C in a nitrogen atmosphere.
[0059] The thickness of the dielectric layer after firing was 2.0 μm. The thickness of the dielectric layer was measured by polishing the cross section shown in Figure 6 with a polishing machine, and measuring the length of 20 points from each of five different fields of view using images of the cross section taken with a SEM (Scanning Electron Microscope), and averaging the measurements for a total of 100 points.
[0060] FIG. 6 is an SEM image of the laminated cross section of the dielectric layer 11 and the internal electrode layer 12 in the capacitance region. As shown in FIG. 6, the crystal grain size is almost uniform in the dielectric layer 11 in the capacitance region. This is believed to be because abnormal grain growth is suppressed by setting the Zr / Ti atomic concentration ratio to 0.02 or more and 0.10 or less. The median diameter of the crystal grains in the dielectric layer 11 in the capacitance region was 200 nm. The median diameter was derived from a total of 500 pieces of data, by polishing the cross section shown in FIG. 6 with a polishing machine in the same manner as for the thickness of the dielectric layer described above, and measuring the length of 100 particles from each of five different fields of view using images of the cross section taken with an SEM.
[0061] FIG. 7 is a TEM (Transmission Electron Microscope) image of the dielectric layer of the capacitance region. As shown in FIG. 7, a core portion 31 and a shell portion 32 covering the core portion 31 were confirmed in the dielectric layer of the capacitance region after firing. FIG. 8(a) shows the measurement result of a TEM-EDS (Energy Dispersive X-ray Spectroscopy) analysis of the shell portion 32. FIG. 8(b) shows the measurement result of a TEM-EDS analysis of the core portion 31. As shown in FIG. 8(a) and FIG. 8(b), it can be seen that the Zr concentration is higher in the shell portion 32 than in the core portion 31. Eu was also confirmed in the core portion 31.
[0062] The X8R characteristics were measured at 1 kHz and 0.5 Vrms in the range of -55°C to 150°C. The dielectric constant was calculated from the capacitance at 25°C, the thickness of the dielectric, and the electrode area. The accelerated life was evaluated by testing 20 samples at 170°C and 125 V until all of them failed, and the average time was taken as the life value. Table 1 shows the dielectric constant, accelerated life test results, and X8R characteristics. For the relative dielectric constant ε, a pass was judged as "good" if it was 1500 or more, and a fail was judged as "x" if it was less than 1500. For the accelerated life, a pass was judged as "good" if it was 3000 min or more, and a fail was judged as "x" if it was less than 3000 min. For the temperature characteristics, a pass was judged as "good" if the X8R characteristics were met, and a fail was judged as "x" if the X8R characteristics were not met. If all three of these items were passed, the overall judgement was a pass (O), and if even one was failed, the overall judgement was a fail (X).
[0063] The overall evaluation of Example 1 was "good". This is because at least one of the crystal grains in the dielectric layer of the capacitance region has a core-shell structure including a core portion mainly composed of barium titanate and a shell portion mainly composed of barium titanate and having a higher Zr concentration than the core portion, the Zr / Ti atomic concentration ratio in the dielectric layer of the capacitance region is 0.02 to 0.10, the Eu / Ti atomic concentration ratio is 0.001 to 0.03, the Mn / Ti atomic concentration ratio is 0.005 to 0.05, the total atomic concentration of other rare earth elements is smaller than the atomic concentration of Eu, and the median diameter of the crystal grains in the dielectric layer of the capacitance region is 200 nm to 400 nm, which is believed to be the reason that both a long life and excellent capacitance-temperature characteristics can be achieved.
[0064] Comparative Example 1 In Comparative Example 1, Yb was used instead of Eu. The other conditions were the same as those in Example 1.
[0065] Comparative Example 2 In Comparative Example 2, Ho was used instead of Eu. The other conditions were the same as in Example 1.
[0066] Comparative Example 3 In Comparative Example 3, Dy was used instead of Eu. The other conditions were the same as in Example 1.
[0067] Comparative Example 4 In Comparative Example 4, Tb was used instead of Eu. The other conditions were the same as in Example 1.
[0068] Comparative Example 5 In Comparative Example 5, Gd was used instead of Eu. The other conditions were the same as in Example 1.
[0069] Comparative Example 6 In Comparative Example 6, Nd was used instead of Eu. The other conditions were the same as in Example 1.
[0070] Comparative Example 7 In Comparative Example 7, Pr was used instead of Eu. The other conditions were the same as in Example 1.
[0071] Comparative Example 8 In Comparative Example 8, Ce was used instead of Eu. The other conditions were the same as in Example 1.
[0072] Comparative Example 9 In Comparative Example 9, Eu was replaced with La. The other conditions were the same as those in Example 1.
[0073] For Comparative Examples 1 to 9, the relative dielectric constant, accelerated life, and X8R characteristics were measured in the same manner as in Example 1, and an overall judgment was made. The accelerated life was judged to be unacceptable in all of Comparative Examples 1 to 9. This is believed to be because a rare earth element other than Eu was used. Moreover, the X8R characteristics were not satisfied in all of Comparative Examples 2 to 9. This is believed to be because a rare earth element other than Eu was used.
[0074] Comparative Example 10 In Comparative Example 10, the median diameter of the crystal grains in the dielectric layer in the capacitance region was set to 100 nm by adjusting the firing conditions, etc. The other conditions were the same as in Example 1.
[0075] Example 2 In Example 2, the median diameter of the crystal grains in the dielectric layer in the capacitance region was set to 300 nm by adjusting the firing conditions, etc. The other conditions were the same as those in Example 1.
[0076] Example 3 In Example 3, the median diameter of the crystal grains in the dielectric layer in the capacitance region was set to 400 nm by adjusting the firing conditions, etc. The other conditions were the same as those in Example 1.
[0077] Comparative Example 11 In Comparative Example 11, the median diameter of the crystal grains in the dielectric layer in the capacitance region was set to 500 nm by adjusting the firing conditions, etc. The other conditions were the same as those in Example 1.
[0078] For Examples 2 and 3 and Comparative Examples 10 and 11, the relative dielectric constant, accelerated life, and X8R characteristics were measured and comprehensively judged in the same manner as in Example 1. In Examples 2 and 3, the comprehensive judgment was judged to be "good". This is because at least one of the crystal grains in the dielectric layer of the capacitance region has a core-shell structure having a core part mainly composed of barium titanate and a shell part mainly composed of barium titanate and having a higher Zr concentration than the core part, the Zr / Ti atomic concentration ratio in the dielectric layer of the capacitance region is 0.02 to 0.10, the Eu / Ti atomic concentration ratio is 0.001 to 0.03, the Mn / Ti atomic concentration ratio is 0.005 to 0.05, the total atomic concentration of other rare earth elements is smaller than the atomic concentration of Eu, and the median diameter of the crystal grains in the dielectric layer of the capacitance region is 200 nm to 400 nm, which is considered to be the reason that both a long life and excellent capacitance-temperature characteristics can be achieved. In contrast, the temperature characteristics were unacceptable in Comparative Examples 10 and 11. This is believed to be because the median diameter of the crystal grains in the dielectric layer of the capacitance region was less than 200 nm or exceeded 400 nm, resulting in a large high temperature change rate of capacitance.
[0079] Comparative Example 12 In Comparative Example 12, the Zr / Ti atomic concentration ratio was set to 0.01. The median diameter of the crystal grains in the dielectric layer in the capacitance region was set to 800 nm by adjusting the firing conditions, etc. The other conditions were the same as those in Example 1.
[0080] Example 4 In Example 4, the Zr / Ti atomic concentration ratio was set to 0.02. The other conditions were the same as those in Example 1.
[0081] Example 5 In Example 5, the Zr / Ti atomic concentration ratio was set to 0.06. The other conditions were the same as those in Example 1.
[0082] Example 6 In Example 6, the Zr / Ti atomic concentration ratio was set to 0.08. The other conditions were the same as those in Example 1.
[0083] Example 7 In Example 7, the Zr / Ti atomic concentration ratio was set to 0.10. The other conditions were the same as those in Example 1.
[0084] Comparative Example 13 In Comparative Example 13, the Zr / Ti atomic concentration ratio was set to 0.20. The other conditions were the same as those in Example 1.
[0085] For Examples 4 to 7 and Comparative Examples 12 and 13, the relative dielectric constant, accelerated life, and X8R characteristics were measured and comprehensively judged in the same manner as in Example 1. In Examples 4 to 7, the comprehensive judgment was judged to be "good". This is because at least one of the crystal grains in the dielectric layer of the capacitance region has a core-shell structure including a core portion mainly composed of barium titanate and a shell portion mainly composed of barium titanate and having a higher Zr concentration than the core portion, the Zr / Ti atomic concentration ratio in the dielectric layer of the capacitance region is 0.02 to 0.10, the Eu / Ti atomic concentration ratio is 0.001 to 0.03, the Mn / Ti atomic concentration ratio is 0.005 to 0.05, the total atomic concentration of other rare earth elements is smaller than the atomic concentration of Eu, and the median diameter of the crystal grains in the dielectric layer of the capacitance region is 200 nm to 400 nm, which is considered to be the reason that both a long life and excellent capacitance-temperature characteristics can be achieved. In contrast, in Comparative Example 12, the accelerated life and temperature characteristics were unacceptable. This is believed to be because the Zr concentration was low, and the core-shell structure described in Figures 4(a) and 4(b) could not be maintained, localized abnormal grain growth occurred, and the life was not expressed, and the X8R characteristics were not satisfied. Figure 9 is an SEM image of the laminated cross section of the dielectric layer 11 and the internal electrode layer 12 in the capacitance region for Comparative Example 12. As shown in Figure 9, it was confirmed that abnormal grain growth occurred in the dielectric layer in the capacitance region. In Comparative Example 13, the relative dielectric constant and temperature characteristics were unacceptable. This is believed to be because the relative dielectric constant was reduced due to the high Zr concentration.
[0086] (Comparative Example 14) In Comparative Example 14, the Eu / Ti atomic concentration ratio was set to 0.0005. The other conditions were the same as those in Example 1.
[0087] Example 8 In Example 8, the Eu / Ti atomic concentration ratio was set to 0.001. The other conditions were the same as those in Example 1.
[0088] Example 9 In Example 9, the Eu / Ti atomic concentration ratio was set to 0.005. The other conditions were the same as those in Example 1.
[0089] Example 10 In Example 10, the Eu / Ti atomic concentration ratio was set to 0.02. The other conditions were the same as those in Example 1.
[0090] Example 11 In Example 11, the Eu / Ti atomic concentration ratio was set to 0.03. The other conditions were the same as those in Example 1.
[0091] Comparative Example 15 In Comparative Example 15, the Eu / Ti atomic concentration ratio was set to 0.04. The other conditions were the same as those in Example 1.
[0092] For Examples 8 to 11 and Comparative Examples 14 and 15, the relative dielectric constant, accelerated life, and X8R characteristics were measured and comprehensively judged in the same manner as in Example 1. In Examples 8 to 11, the comprehensive judgment was judged to be "good". This is considered to be because at least one of the crystal grains in the dielectric layer of the capacitance region has a core-shell structure including a core portion mainly composed of barium titanate and a shell portion mainly composed of barium titanate and having a higher Zr concentration than the core portion, the Zr / Ti atomic concentration ratio in the dielectric layer of the capacitance region is 0.02 to 0.10, the Eu / Ti atomic concentration ratio is 0.001 to 0.03, the Mn / Ti atomic concentration ratio is 0.005 to 0.05, the total atomic concentration of other rare earth elements is smaller than the atomic concentration of Eu, and the median diameter of the crystal grains in the dielectric layer of the capacitance region is 200 nm to 400 nm, which allows both a long life and excellent capacitance-temperature characteristics to be achieved. In contrast, the accelerated lifetime of Comparative Example 14 was unacceptable. This is believed to be because the amount of Eu added was small, and a sufficiently long lifetime could not be achieved. The accelerated lifetime of Comparative Example 15 was also unacceptable. This is believed to be because the amount of Eu added was large, and a long lifetime could not be achieved by semiconductorization.
[0093] Comparative Example 16 In Comparative Example 16, the Mn / Ti atomic concentration ratio was set to 0.001. The other conditions were the same as those in Example 1.
[0094] Example 12 In Example 12, the Mn / Ti atomic concentration ratio was set to 0.005. The other conditions were the same as those in Example 1.
[0095] (Example 13) In Example 13, the Mn / Ti atomic concentration ratio was set to 0.01. The other conditions were the same as those in Example 1.
[0096] Example 14 In Example 14, the Mn / Ti atomic concentration ratio was set to 0.02. The other conditions were the same as those in Example 1.
[0097] Example 15 In Example 15, the Mn / Ti atomic concentration ratio was set to 0.05. The other conditions were the same as those in Example 1.
[0098] (Comparative Example 17) In Comparative Example 17, the Mn / Ti atomic concentration ratio was set to 0.1. The other conditions were the same as those in Example 1.
[0099] For Examples 12 to 15 and Comparative Examples 16 and 17, the relative dielectric constant, accelerated life, and X8R characteristics were measured and comprehensively judged in the same manner as in Example 1. In Examples 12 to 15, the comprehensive judgment was judged to be "good". This is because at least one of the crystal grains in the dielectric layer of the capacitance region has a core-shell structure having a core part mainly composed of barium titanate and a shell part mainly composed of barium titanate and having a higher Zr concentration than the core part, the Zr / Ti atomic concentration ratio in the dielectric layer of the capacitance region is 0.02 to 0.10, the Eu / Ti atomic concentration ratio is 0.001 to 0.03, the Mn / Ti atomic concentration ratio is 0.005 to 0.05, the total atomic concentration of other rare earth elements is smaller than the atomic concentration of Eu, and the median diameter of the crystal grains in the dielectric layer of the capacitance region is 200 nm to 400 nm, which is considered to be the reason that both a long life and excellent capacitance-temperature characteristics can be achieved. In contrast, the accelerated lifetime was unacceptable in Comparative Example 16. This is believed to be because there was a shortage of acceptors and the dielectric layer became semiconductive. The accelerated lifetime was also unacceptable in Comparative Example 17. This is believed to be because there was an excess of acceptors. [Table 1]
[0100] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to such specific embodiments, and various modifications and variations are possible within the scope of the gist of the present invention described in the claims. [Explanation of symbols]
[0101] 10 Stacked Chip 11 Dielectric layer 12 Internal electrode layer 13 Cover Layer 14 Capacity area 15 End Margin 16 Side Margin 20a,20b external electrode 100 Multilayer ceramic capacitors
Claims
1. The material contains a plurality of crystal grains mainly composed of barium titanate, Contains Zr, Eu, and Mn as additives; At least one of the plurality of crystal particles has a core-shell structure including a core portion mainly composed of barium titanate and a shell portion mainly composed of barium titanate and having a higher Zr concentration than the core portion, The Zr / Ti atomic concentration ratio is 0.02 or more and 0.10 or less, The Eu / Ti atomic concentration ratio is 0.001 or more and 0.03 or less, the Mn / Ti atomic concentration ratio is 0.005 or more and 0.05 or less; The total atomic concentration of the other rare earth elements is smaller than the atomic concentration of Eu, A dielectric material characterized in that the median diameter of the plurality of crystal grains is 200 nm or more and 400 nm or less.
2. 2. The dielectric material according to claim 1, wherein no rare earth elements other than Eu are added.
3. The laminated structure has a substantially rectangular parallelepiped shape in which dielectric layers and internal electrode layers are alternately laminated, and the laminated internal electrode layers are alternately exposed on two different surfaces, a multilayer ceramic capacitor comprising: a dielectric layer in a capacitance region where internal electrode layers exposed on two different surfaces face each other, the dielectric layer comprising a plurality of crystal grains mainly composed of barium titanate, and containing Zr, Eu, and Mn as additives; at least one of the plurality of crystal grains having a core portion mainly composed of barium titanate and a shell portion mainly composed of barium titanate and having a higher Zr concentration than the core portion; a Zr / Ti atomic concentration ratio of 0.02 to 0.10, an Eu / Ti atomic concentration ratio of 0.001 to 0.03, and an Mn / Ti atomic concentration ratio of 0.005 to 0.05; a total atomic concentration of other rare earth elements is smaller than the atomic concentration of Eu; and a median diameter of the plurality of crystal grains is 200 nm to 400 nm.
4. 4. The multilayer ceramic capacitor according to claim 3, which satisfies X8R characteristics.
5. A method for producing a dielectric, comprising: a dielectric green sheet containing barium titanate powder, containing Zr, Eu and Mn as additives, having a Zr / Ti atomic concentration ratio of 0.02 or more and 0.10 or less, an Eu / Ti atomic concentration ratio of 0.001 or more and 0.03 or less, an Mn / Ti atomic concentration ratio of 0.005 or more and 0.05 or less, and having a total atomic concentration of other rare earth elements smaller than the atomic concentration of Eu, and heating the dielectric green sheet at a heating rate of 5000°C / h or more and 10000°C / h or less to obtain a dielectric containing a plurality of crystal particles mainly composed of barium titanate, the plurality of crystal particles having a median diameter of 200 nm or more and 400 nm or less.
6. a step of obtaining a ceramic laminate by stacking a plurality of lamination units, each having a metal conductive paste printed thereon, on a dielectric green sheet that contains barium titanate powder, Zr, Eu and Mn as additives, a Zr / Ti atomic concentration ratio of 0.02 or more and 0.10 or less, a Eu / Ti atomic concentration ratio of 0.001 or more and 0.03 or less, a Mn / Ti atomic concentration ratio of 0.005 or more and 0.05 or less, and a total atomic concentration of other rare earth elements being lower than the atomic concentration of Eu; 1. A method for producing a multilayer ceramic capacitor, comprising: heating the ceramic laminate at a heating rate of 5,000° C. / h or more and 10,000° C. / h or less, and firing the ceramic laminate so as to form a dielectric layer from the dielectric green sheets, the dielectric layer containing a plurality of crystal grains mainly composed of barium titanate, the plurality of crystal grains having a median diameter of 200 nm or more and 400 nm or less.
Citation Information
Patent Citations
Laminated type ceramic capacitor
JP2006013206A
Dielectric ceramic particles and dielectric ceramic
JP2015187969A
Dielectric ceramic composition and ceramic electronic component
JP2016169129A
Dielectric ceramic composition and ceramic electronic component
JP2016169130A
Dielectric ceramic composition and ceramic electronic component comprising the same
JP2017114751A